The near-peer tutoring programme: embracing the ‘doctors-to-teach’ philosophy – a comparison of the effects of participation between the senior and junior near-peer tutors - Liew, Siaw-Cheok (Med Educ Online, 2015)
BACKGROUND: While there is an increasing pool of literature documenting the benefits of near-peer tutoring programme, little is known about the benefits for junior and senior peer tutors. Knowledge of the peer tutors’ perceived benefits at different levels of seniority will aid in the development of a near-peer tutoring programme that will better fulfil both curricula and personal aspirations of near-peer tutors. We, therefore, investigated the perceived benefits of participation in a near-peer tutoring programme for junior as well as senior near-peer tutors. METHODS: Pre- and post-participation questionnaires were distributed to near-peer tutors after their clinical skills teaching sessions with Phase I undergraduate medical students. The Peer Tutor Assessment Instrument questionnaires were distributed to the 1) students, and to the 2) near-peer tutors (junior and senior) after each teaching and learning session for self-evaluation. RESULTS: The senior near-peer tutors felt that their participation in the programme had enhanced their skills (p=0.03). As a whole, the near-peer tutors were more motivated (Pre 5.32±0.46; Post 5.47±0.50; p=0.210) to participate in future teaching sessions but did not expect that having teaching experiences would make teaching as their major career path in the future (Pre 4.63±1.07; Post 4.54±0.98; p=0.701). The senior near-peer tutors were evaluated significantly higher by the students (p=0.0001). Students’ evaluations of near-peer tutors on the domain of critical analysis was higher than self-evaluations (p=0.003). CONCLUSIONS: Generally, the near-peer tutors perceived that they have benefited most in their skills enhancement and these near-peer tutors were scored highly by the students. However, senior near-peer tutors do not perceive that the programme has a lasting impact on their choice of career path.